Action observation treatment improves gait ability in subacute to convalescent stroke patients. (May 2020) - Hioka, Akemi; Tada, Yoshiteru; Kitazato, Keiko; Akazawa, Naoki; Takagi, Yasushi; Nagahiro, Shinji
Highlights: We investigated the effects of action observation treatment (AOT) on gait ability. The effect of AOT was investigated in patients with subacute to convalescent stroke. AOT had no effect in patients who could not walk independently. AOT improved gait ability in patients who were able to walk independently. AOT may be an effective therapy for patients with stroke who can walk independently. Abstract: The aim of this study was to investigate the effects of action observation treatment (AOT) on gait ability in patients with subacute to convalescent stroke. Sixteen patients with subacute stroke were divided into a control group (n = 8) and AOT group (n = 8) when admitted to the convalescent ward. The control group received a conventional rehabilitation only. In addition to conventional rehabilitation, the AOT received AOT for 3 months (30 min per day 5 times per week). The AOT involved observing the action of another subject in a comfortable gait situation from the front, sides, and back via video and conducting the actual action. All participants were assessed during the main-assessment period, which included a baseline (i.e., when admitted to the convalescent ward) and 1, 2, and 3 months after baseline. The sub-assessment period at 2 and 3 months after baseline was conducted with participants who could walk independently. The main outcomes of the main-assessment and sub-assessment periods were Functional Ambulation Classification (FAC) and the 10-m walk test (10MWT), respectively. With respect to the FAC, we used a split plot design analysis of covariance to test the interaction between assessment time and group. There was no significant interaction between assessment time and group in FAC. However, a significant improvement of the 10MWT in the sub-assessment period was observed in the AOT group, but not the control group. Our results indicate that AOT may be an effective therapy for patients with subacute to convalescent stroke who can walk independently.